Deconstructing the Concept of Ahlul Kitab: A Critical Analysis of Muhammad Arkoun's Thought in the Context of Interfaith Marriage - Nor Ichwan, Moh; Ali Abdulghani, Naser; Shafa Maharani, Atika (IAIN Kendari, 2025)
This study examines Muhammad Arkoun's thoughts on the deconstruction of the concept of Ahlul Kitab and its relevance in the context of a multireligious society. Using a qualitative approach and critical analysis method, this study explores Arkoun's critique de la raison islamique method, which combines hermeneutics, history, and social analysis to dismantle the traditional understanding of the People of the Book. The research findings show that Arkoun offers an inclusive perspective through the concept of the People of the Book, which expands the scope of biblical groups beyond Jews and Christians. This approach challenges rigid theological narratives and opens space for a reinterpretation of Islamic law more adaptive to modern social realities. In addition, Arkoun emphasizes the importance of gender equality in marriage, criticizing the patriarchal bias in classical interpretations of Islamic law. Although Arkoun's thought contributes significantly to the discourse of pluralism and interfaith dialogue, the concept of the People of the Book has been criticized for potentially blurring religious identity and eroding the authority of sacred texts. This article recommends further research to examine the practical implementation of Arkoun's thought, especially in the context of non-Western Muslim societies such as Indonesia, as well as a deeper exploration of the balance between inclusivity and theological consistency. Thus, Arkoun's thought offers a significant methodological perspective for developing Islamic family law more responsive to the challenges of a modern pluralistic society.